2014 International Symposium on Computer, Consumer and Control 2014
DOI: 10.1109/is3c.2014.305
|View full text |Cite
|
Sign up to set email alerts
|

An App for Promoting Health and Local Tourism

Abstract: The main purpose of this study is to develop a smartphone App under Android platform by integrating GPS to provide local tourism information and guide tourists to their interested sites. The provided folk-cultural information is also adopted for educational purpose. Extended technology acceptance model (TAM) was used to evaluate the usefulness and behavior intention of the developed system. Most users agreed that the system is useful for tourism promotion and folk-culture education. They also showed strong int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The previous literature revealed that there has been little research attention devoted to the study of ecotourism emphasizing young people although the topic is significant in terms of the impact on future ecotourism (Chao et al, 2014;Halvatzaras & Kabassi, 2016;Meiliana et al, 2017;Nitti et al, 2017;Reisinger & Mavondo, 2002;Ruíz et al, 2017;World Tourism Organization, 2010). Nevertheless, the studies by Cini et al (2015), Kasim and Wickens (2018), as well as the study of Sangpikul and Batra (2007) relating to ecotourism and young Thais suggest that ecotourism is a new and important trend in tourism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous literature revealed that there has been little research attention devoted to the study of ecotourism emphasizing young people although the topic is significant in terms of the impact on future ecotourism (Chao et al, 2014;Halvatzaras & Kabassi, 2016;Meiliana et al, 2017;Nitti et al, 2017;Reisinger & Mavondo, 2002;Ruíz et al, 2017;World Tourism Organization, 2010). Nevertheless, the studies by Cini et al (2015), Kasim and Wickens (2018), as well as the study of Sangpikul and Batra (2007) relating to ecotourism and young Thais suggest that ecotourism is a new and important trend in tourism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, tourism services can use smart technology to offer their services and gain information through user feedback to ensure service sustainability. Finally, Destination marketing organizations, which are responsible for providing information to potential visitors can use smart technologies to encourage visitors to purchase destination-related products (Chao et al, 2014;Halvatzaras & Kabassi, 2016;Meiliana et al, 2017;Nitti et al, 2017;Ruíz et al, 2017).…”
Section: Role Of Smart Ecotourism-related Applicationmentioning
confidence: 99%
“…Blockchain has the potential to revolutionize the way the industry operates by enabling secure, transparent, and decentralized transactions [22]. These technologies are coming together to provide innovative capabilities and services including forecasting tourism demand [23], mining tourist locations, pathways, and travel itineraries [24], the visualization of tourist mobility activity patterns, identifying tourist congestion zones and tourist routes in specific areas [25], measuring tourist satisfaction [26], support for decision-making [27], identifying factors related to tourist satisfaction [28], integration of the Android platform and GPS services for guiding tourists to their preferred sites [29], augmented reality for historical tourism using mobile and smart devices [30,31], and more.…”
Section: Technologies and Their Impact On Tourismmentioning
confidence: 99%
“…Blockchain has the potential to revolutionize the way the industry operates by enabling secure, transparent, and decentralized transactions [11]. These technologies are coming together to provide innovative capabilities and services including forecasting tourism demand [12], mining tourist locations, pathways, and travel itineraries [13], visualization of tourist mobility activity patterns, identifying tourist congestion zones and tourist routes in specific areas [14], measuring tourist satisfaction [15], support for decision-making [16], identifying factors related to tourist satisfaction [17], integration of the Android platform and GPS services for guiding tourists to their preferred sites [18], augmented reality for historical tourism using mobile and smart devices [19], [20], and more.…”
Section: Technologies and Their Impact On Tourismmentioning
confidence: 99%
“…Looking at the scientific papers that belong to this parameter we were able to find several topics that capture various mobile application services. These services include integration of the Android platform and GPS services in guiding tourists to their preferred sites [18], augmented reality for historical tourism using mobile and smart devices [19], [20], the use of Mobile Applications for tracking tourist travel experiences [241], determining different types of tourists mobility and providing location-based services [9], [242], and implementing QR systems for shopping centers [243].…”
Section: Mobile Applicationsmentioning
confidence: 99%